2011
DOI: 10.1097/mbp.0b013e328346d603
|View full text |Cite
|
Sign up to set email alerts
|

Age and the difference between awake ambulatory blood pressure and office blood pressure

Abstract: Background Ambulatory blood pressure (ABP) is a better predictor of adverse cardiovascular events than office BP (OBP). Due to the extensive literature on the “white coat effect”, it is widely believed that ABP tends to be lower than OBP, with statements to this effect in JNC VII. However, recent evidence suggests that the difference varies systematically with age. Methods We searched PubMed to identify population studies, published before April 2009, which assessed office BP and either ABP or home BP. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
(93 reference statements)
7
31
2
Order By: Relevance
“…A significant influence of age on the ABP-HBP difference was also shown, with elderly patients showing smaller difference than the younger ones. This finding is in line with a recent meta-analysis by Ishikawa et al, 15 which showed no difference between awake ABP and HBP in older subjects, whereas in the younger HBP was lower.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A significant influence of age on the ABP-HBP difference was also shown, with elderly patients showing smaller difference than the younger ones. This finding is in line with a recent meta-analysis by Ishikawa et al, 15 which showed no difference between awake ABP and HBP in older subjects, whereas in the younger HBP was lower.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent metaanalysis of 27 studies (n¼12 127), Ishikawa et al 15 showed that increasing age, female gender and not using oscillometric device for clinic BP, predispose to WCP detecting by ABP. In a study of 5716 subjects, white coat hypertension detected by ABP was more common among older adults, females and non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 More recently, a meta-analysis of population studies on adults and children performed in 1990 to 2009 and a recent study from the IDACO (International Database on Ambulatory Blood Pressure and Cardiovascular Outcomes) on 13 population-based cohorts have described higher clinic than daytime BP only in older subjects, but higher daytime than clinic BP in subjects under the age of 50 years. 14,15 Similar results (daytime BP higher than clinic BP) have been described in children and adolescents. 16,17 Most of these previous studies were centered on untreated populations, 5,14,15 and most prior clinical studies have been small (<200 subjects).…”
Section: Hypertensionsupporting
confidence: 72%
“…14,15 Similar results (daytime BP higher than clinic BP) have been described in children and adolescents. 16,17 Most of these previous studies were centered on untreated populations, 5,14,15 and most prior clinical studies have been small (<200 subjects). [6][7][8][9]11 Thus, little is known about the age relationship between clinic and ambulatory BP in large cohorts of hypertensive patients in usual clinical practice, especially in primary care, where most treated and untreated hypertensive people are cared for.…”
Section: Hypertensionsupporting
confidence: 72%
“…Our results were robust to sensitivity analyses where different definitions of ambulatory hypertension were used. The inverse relationship in younger individuals has received little attention previously, [11][12][13] and most available studies mainly focused on the direct relationship between age and the white coat response. 14,15 As in our work, these studies found that the white coat response increases with increasing age and that it was stronger among individuals with office hypertension.…”
Section: Discussionmentioning
confidence: 99%